EFFECT OF REPRODUCTIVE HEALTH EDUCATION ON ADOLESCENT KNOWLEDGE LEVEL ABOUT UNWANTED PREGNANCY IN PALALANGON VILLAGE, CIANJUR REGENCY - Natalia, Lidya; Hariningsih, Wintari; Majiah, Isna Tresna (Journal of Vocational Nursing, 2020)
Introduction: Adolescence is one of the stages of life. Adolescents hope that the future of the nation needs to be taken care of physically and mentally and socially as a whole (Law No. 61/2014 about Reproductive Health), as well as all matters relating to the system and functions and processes of reproduction. In Indonesia the incidence of unwanted pregnancy in adolescents has a percentage of 17%. Adolescent reproductive health education about unwanted pregnancy is very important to be known by adolescents as one of the preventions of unwanted pregnancy. The purpose of this study was to analyze the effect of reproductive health education on adolescent knowledge level about unwanted pregnancy in adolescent Palalangon. Methods : The study design uses a pre-experimental design one group pretest-posttest design, using a purposive sampling technique and obtained a total sampling of 39 respondents. The method of data collection is done by using a questionnaire statement totaling 25 items. Results : The results showed that 38 respondents (97.4%) before the health education program was knowledgeable and less than 1 person (2.6%) knowledgeable, whereas after health education all respondents had a good knowledge with a percentage (100%). The conclusion of Wilcoxon's statistical test analysis results obtained sig (0.00) <sig (0.05) which means that there is an effect of adolescent reproductive health education between knowledge before and after health education. Conclusion: Health care workers are expected to be able to carry out health education specifically on adolescent reproductive health as one of the preventions of unwanted pregnancy problems among adolescents